1998
DOI: 10.1063/1.476788
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical characterization of the quartet states of the SO+ molecular ion

Abstract: A theoretical study of the electronic structure and spectroscopic properties of the low-lying electronic states of the molecule SiB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Cossart et al [13] performed an ab initio calculations using the self-consistent field (SCF) method followed by configuration interaction (CI) to interpret their observed spectra. Ornellas et al [19] reported a theoretical characterization of quartet states of SO + using the internally contracted multi-reference configuration interaction approach and natural orbits. Recently, Houria et al [9] carried out a spectroscopic and spin-orbit calculations on SO + using highly correlated ab initio methods.…”
Section: Introductionmentioning
confidence: 99%
“…Cossart et al [13] performed an ab initio calculations using the self-consistent field (SCF) method followed by configuration interaction (CI) to interpret their observed spectra. Ornellas et al [19] reported a theoretical characterization of quartet states of SO + using the internally contracted multi-reference configuration interaction approach and natural orbits. Recently, Houria et al [9] carried out a spectroscopic and spin-orbit calculations on SO + using highly correlated ab initio methods.…”
Section: Introductionmentioning
confidence: 99%
“…He proposes that a spin-orbit coupling between the b 4 AE À and repulsive I 4 AE + states leads to the predissociation. However, as pointed out by Ornellas & Borin (1998), according to Figure 3 of Cosby's study, these two states cross near v 0 ¼ 12, and an effective coupling would be expected to occur only for v 0 ¼ 12. For the other vibrational levels, this effect would be practically negligible.…”
Section: Sulfoxide Ion (So + )mentioning
confidence: 84%
“…The potential energy curves of the 1 4 AE þ and a 4 Å states calculated by Ornellas & Borin (1998) by means of the ICMRCI method are used for r > 2:2a 0 (Fig. 2).…”
Section: Sulfoxide Ion (So + )mentioning
confidence: 99%
See 2 more Smart Citations